2020
DOI: 10.1186/s40164-020-00188-w
|View full text |Cite
|
Sign up to set email alerts
|

Molecular insights into pathogenesis and targeted therapy of peripheral T cell lymphoma

Abstract: Peripheral T-cell lymphomas (PTCLs) are biologically and clinically heterogeneous diseases almost all of which are associated with poor outcomes. Recent advances in gene expression profiling that helps in diagnosis and prognostication of different subtypes and next-generation sequencing have given new insights into the pathogenesis and molecular pathway of PTCL. Here, we focus on a broader description of mutational insights into the common subtypes of PTCL including PTCL not other specified type, angioimmunobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 119 publications
0
27
0
Order By: Relevance
“…As reported in other studies, the representative genetic alterations to induce a robust T follicular helper phenotype ( RHOA, IDH2, and DNMT3A ) of AITL also appeared in other TFH lymphomas [ 24 ]. However, other mutation profiles that play an essential role in T-cell receptor (TCR) signaling, transcription factors, and tumor suppressors were shared evenly between AITL, other TFH lymphomas, and PTCL-NOS [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…As reported in other studies, the representative genetic alterations to induce a robust T follicular helper phenotype ( RHOA, IDH2, and DNMT3A ) of AITL also appeared in other TFH lymphomas [ 24 ]. However, other mutation profiles that play an essential role in T-cell receptor (TCR) signaling, transcription factors, and tumor suppressors were shared evenly between AITL, other TFH lymphomas, and PTCL-NOS [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…HOXA1 activates nuclear factor κ‐light‐chain‐enhancer of activated B cells (NF‐κB) to modulate the tumour necrosis factor‐α/NF‐κB signalling pathway 46 or regulates tumour progression in gastric cancer via cyclin D1 45 . The deletion of CDKN2A was reported in some adult PTCL, 11–13 while our observations indicated that it is limited to EBV – PTCL [PTCL‐NOS and subcutaneous panniculitis‐like T‐cell lymphoma (SPTCL)], but not EBV + PTCL, in paediatric PTCL.…”
Section: Discussionmentioning
confidence: 70%
“…To refine the classification of PTCL even more, further clarification of the molecular pathogenesis will be required 11–14 . A subset of PTCL‐NOS shares some of the recurrent genetic alterations found in angioimmunoblastic T‐cell lymphoma (AITL), such as mutations affecting ten–eleven translocation methylcytosine dioxygenase 2 ( TET2 ), DNA methyltransferase 3α ( DNMT3A ) and Ras homolog family member A ( RHOA ), 15 and has been recommended to be classified as PTCL‐NOS with a T‐follicular helper (TFH) cell phenotype as a provisional entity (TFH PTCL‐NOS) in the revised WHO classification 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…AITL is a special subtype of peripheral T-cell lymphoma that originates from follicular helper T cells (TFH), often with fever, night sweats, weight loss, lymphadenopathy, skin rash, and other clinical manifestations 3 Skin involvement is one of the most common extranodal manifestations of the disease 4 Due to the heterogeneity of AITL, most cases do not get diagnosed until weeks or months after the onset of symptoms.…”
Section: Discussionmentioning
confidence: 99%